2021
DOI: 10.1021/acsami.1c04903
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Role of Point Defects in Perovskite Nickelate Electrocatalysts

Abstract: Low-cost transition-metal oxide is regarded as a promising electrocatalyst family for an oxygen evolution reaction (OER). The classic design principle for an oxide electrocatalyst believes that point defect engineering, such as oxygen vacancies (VO ..) or heteroatom doping, offers the opportunities to manipulate the electronic structure of material toward optimal OER activity. Oppositely, in this work, we discover a counterintuitive phenomenon that both VO .. and an aliovalent dopant (i.e., proton (H+)) in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
(107 reference statements)
1
9
0
Order By: Relevance
“…Protons play an important role in tuning the physical and chemical properties of perovskite nickelates ( R NiO 3 ), including transport properties, optical properties, ion migration and ionic conductivity, (electro-)­catalytic activity, etc. Tuning the proton concentration via an ionic liquid gating technique has already attracted a great deal of attention from the functional oxide community, due to its ease of implementation and wide range of tunability in oxide properties .…”
mentioning
confidence: 99%
“…Protons play an important role in tuning the physical and chemical properties of perovskite nickelates ( R NiO 3 ), including transport properties, optical properties, ion migration and ionic conductivity, (electro-)­catalytic activity, etc. Tuning the proton concentration via an ionic liquid gating technique has already attracted a great deal of attention from the functional oxide community, due to its ease of implementation and wide range of tunability in oxide properties .…”
mentioning
confidence: 99%
“…According to the current research progress, the alkaline‐earth metals are basically introduced into NNTM‐based oxides to modify their OER and/or HER activity. [ 142–167 ] Furthermore, the incorporation of alkaline‐earth metals mainly leads a fundamental role in the following four aspects. [ 145–165 ] i) Tuning the alkaline‐earth metal species in certain oxides can create lattice defects, which dictates a high conductivity and optimized free adsorption energy toward oxygen intermediates; ii) the alkaline‐earth metal species can gradually leach from the catalysts during catalysis, which will in situ leave pores in the phase reconstructed NNTM‐based (oxy)hydroxides catalysts, conducing to the exposure of active sites; iii) they mediate the formation of NNTM‐species with high oxidation state, thus resulting in the improvement of catalytic activity; and iv) the incorporation of some alkaline‐earth metal species into NNTM‐based phase can alter the morphology during synthesis, such as nanosheet, which is beneficial for the accessibility of reactants to surficial NNTM sites during catalysis.…”
Section: Merits Of S‐ P‐ and F‐block Metals In Water Electrolysismentioning
confidence: 99%
“…Yifei Sun et al found the counterintuitive phenomenon that oxides in perovskite nickelate (NdNiO 3 (NNO)) and a heterovalent dopant (proton (H + )) have quite adverse effects on the intrinsic OER performance. 144 The authors reveal that the introduction of these point defects brings about the reduction of the Ni oxidation state and hybridization of Ni−O orbitals, triggering the interaction between local electron−electron. DFT calculation results show that the OER of nickelate electrocatalyst follows the LOM.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…The OER is a multistep reaction pathway, including the absorption of reactive molecules, transformation of intermediates, and dissociation of product, which is closely associated to the strength of the B–O bond and the coordination structure around the B-site metal in the perovskite. Based on this theory, an unsaturated coordination environment for B–O bonds or B-position atoms is created by introducing anion or cation vacancies into the structure of the perovskite. Ramezanipour et al reported an oxygen-deficient Sr 2 Fe 2 O 6‑δ perovskite, and its intrinsic OER activity is better than those of BSCF and RuO 2 .…”
Section: Strategies For Performance Optimization Of Perovskite Catalystsmentioning
confidence: 99%
See 1 more Smart Citation